ANALISIS KEHALALAN DAGING SAPI DENGAN METODE PORK DETECTION KIT (PDK) DAN TINGKAT KEPEDULIAN KONSUMEN DALAM MENGKONSUMSI DAGING SAPI HALAL - Mardiah, Mardiah; Lia Amalia; Dinda Army Trimelati (Universitas Djuanda, 2020)
Analysis of the halal beef in Bekasi City Market is very necessary to find out whether meat traders do adulteration or not. This study aims to determine whether the meat being sold is contaminated with wild boar meat and to determine the level of consumer concern in consuming halal meat in Bekasi City. The method used in this research is the Pork Detection Kit (PDK) method and the survey method using a questionnaire to the community in Bekasi City. The research sample was taken by using purposive sampling method. The data obtained were analyzed descriptively. The results showed that the beef sold in the Bekasi City market was negative for pork contamination. At the level of consumer concern in consuming halal meat, the results show that 80% of the people in Bekasi City have considered the halal aspect when buying meat for consumption, either fresh meat or frozen meat. Keywords: meat, adulteration, pork detection, halal concern.